Continuous Production of Rotifer Brachionus plicatilis (Müller 1786) in a Helical Tubular Photobioreactor Fed with Algae Nannochloripsis oculata - H. Kargin (Advanced Research in Biological Science Vol. 2, 2023)
Simple microscopic organisms called microalgae use photosynthesis to turn inorganic materials into organic ones by absorbing light. For many aquatic creatures that are crucial for commerce, particularly fish, microalgae are the most important food supply. Aquaculture relies heavily on live feeds, particularly during the larval stages of several commercial marine fish including sea bream, sea bass, turbot, and coral. While some of the algae are indirectly utilized to feed the rotifer, which is an essential meal in the fish’s larval stage, certain fish also ingest microalgae in their adulthood. In marine fish hatcheries, Nannocloropsis sp. (Eustigmatophyceae) is produced as bait for rotifers and to create a ’green water effect’ in larval tanks. Many marine fish larvae find Rotifer to be a great feeding source. Rotifers are an excellent diet for larvae with small mouth openings. Microalgae boost larval survival and growth by transmitting their high fatty acid content to the larva via the rotifer. Taking all of these factors into account, it is critical to develop a safe and suitable production system for the production of rotifers and microalgae from live feed. The adoption of specifically constructed, fully enclosed, and controlled photobioreactors is necessary for continuous microalgae production. The most often utilized type of closed bioreactor is a tubular photobioreactor. Transparent glass or plastic tubes are the main components of tubular photobioreactors. The tubes can be arranged in vertical, horizontal, helical, or inclined orientations depending on their design. In contrast to open ponds, photobioreactors provide advantages such as improved pH and temperature control, better mixing, fewer evaporation losses, more biomass output, and a higher surface-to-volume ratio. Photobioreactors are made to address the drawbacks of open ponds. Additionally, compared to open ponds, there is less chance of contamination, making this environment good for growing a single species of microalgae. The large-scale production of microalgae aims to create low-cost products of high quality. It is vital to compare the main challenges in large-scale culture systems, such as the effective use of light, temperature, hydrodynamic balance in microalgae culture, and culture continuity. Only by supplying proper conditions in the growing medium can each microalgae species thrive optimally. As a result, with high pH and bicarbonate concentrations, Spirulina sp., Chlorella sp. In nutrient-rich media, Dunaliella salina grows best at very high salinity, while Nannochloripsis oculata grows best at 25-30‰ salinity. When the nutritional value of planktonic organisms is evaluated, the amount of food and frequency of feeding appears to be the most important elements influencing the nutritional content and growth values of rotifers. One technique used in algae biotechnology is the continuous culture system. While the development rate in continuous culture systems is ensured by the nutrient support that is continuously added to the medium, it is desirable to achieve balanced environmental conditions by providing the nutrient output from the environment at the same rate. The nutrient liquid delivered to the environment, on the other hand, must be precisely adjusted. In such a system, in addition to continuous and consistent nutritional support, a set quantity of product and by-product outflow from the environment is given, preventing hazardous chemical accumulation that causes growth to cease. As a result, the drawbacks of batch production are mitigated by continuous production. Nannochloropsis oculata algae species were generated in a continuous system and at 30‰ salt concentration utilizing an artificial light source (daylight) in the spiral photobioreactor built for the study. Algae were continuously introduced into the rotifer tank from the helical photobioreactor for two weeks, and the rotifer was harvested within 24 hours. The experiment was carried out three times. Rotifer B. plicatilis cell increases and specific growth rates were studied in a continuous algae system. As a result, in the study, algae grown at maximum density in the spiral photobioreactor’s continuous system were fed to the B. plicatilis tank and harvested daily from the rotifer (B. plicatilis) culture tank for 24 hours. The growth performance of B. plicatilis rose by an average of tenfold during the trial. The findings of this study are expected to be reviewed in order to boost rotifer production in marine fish farms where larval production is carried out, and an increase in product productivity will be attained while ensuring rotifer production continuity.